Review on diagnosis and management of urolithiasis in pregnancy: an ESUT practical guide for urologists - Somani, Bhaskar K.; Dellis, Athanasios; Liatsikos, Evangellos; Skolarikos, Andreas (World journal of urology, 2017)
Purpose Management of urolithiasis in pregnancy can be challenging for most urologists with diagnostic and treatment dilemma to ensure the best outcome for both mother and fetus. We wanted to review the literature for urolithiasis in pregnancy with a practical management guide for urologists. Methods A non-systematic review of literature was carried out for all English language literature using Medline. To ensure a more comprehensive search, the review of diagnosis and management of pregnant patients with urolithiasis was carried out separately, by two authors independently. Due to diagnostic complexity, investigations (US, CT, MRI) carried out were assessed separately. Results Our search included diagnostic studies such as US, CT and MRI (73, 20 and 27 articles, respectively) and management studies (55 articles in total). Details on etiology, radiation risk, safety of various diagnostic modalities, medications and treatment options are covered through an evidence-based approach. We provide a practical guide for urologists in what is clearly a stressful situation for patient and physician alike. Conclusions Urolithiasis in pregnancy needs a careful multidisciplinary management to achieve good outcomes for both mother and baby. Our review shows that a balanced approach for diagnosis and treatment seems to achieve the best outcomes in pregnancy.